(untitled) (Comparative & International Education Series, 2021)
This chapter provides a critical reflection on a selection of tertiary students’ responses in China in the national battle against COVID-19. It explains how tertiary students have responded to the COVID-19 pandemic and why they have responded. Student stories, diaries, and a letter published are reviewed as cases of their response in their national battle against the pandemic. The tertiary students’ response to other national events is also retraced through a diary by the author while participating in higher education of China in the 1990s for further exploration. The impact of Chinese education philosophies, policy, system, and practice on the response to COVID-19 by Chinese tertiary students is explored. The belonging, being, and becoming of tertiary students in China is suggested to be the critical factor for the extensive participation and support by the students in the national battle against the COVID-19 pandemic.